Alginate-hydroxyapatite scaffolds: A comprehensive characterization study - Saanvi Gupta; Suganya Panneer Selvam; Ramya Ramadoss; Sandhya Sundar (Journal of Oral Biology and Craniofacial Research)
Introduction: Alginate has garnered significant attention in regenerative dentistry for its biocompatibility, mechanical strength, and controlled biodegradability. The incorporation of hydroxyapatite enhances its ability to mimic the dentin extracellular matrix, promoting cellular adhesion, proliferation, and mineralization. This study aims to comprehensively assess the structural, chemical, and biological properties of Alg-HA scaffolds to evaluate their potential for dentin regeneration. Methods: Alginate-hydroxyapatite (Alg-HA) scaffolds were synthesized by dissolving sodium alginate (2 % w/v) in distilled water, followed by the incorporation of hydroxyapatite (HA) synthesized via chemical precipitation using calcium nitrate tetrahydrate and ammonium phosphate. The composite solution was homogenized through stirring and ultrasonication before being freeze-dried to fabricate porous scaffolds. Characterization was performed using X-ray Diffraction (XRD) to confirm crystallinity, Fourier Transform Infrared Spectroscopy (FTIR) to verify functional group interactions, and Scanning Electron Microscopy (SEM) with Energy Dispersive X-ray Analysis (EDAX) to analyze morphology and elemental composition. In vitro degradation studies were conducted in simulated body fluid (SBF) to assess scaffold stability by measuring mass loss over time, with additional pH monitoring and SEM analysis for morphological changes. Hemocompatibility was evaluated through hemolysis assays, comparing scaffold-incubated blood samples to positive and negative controls. Results: XRD analysis confirmed the successful incorporation of HA within the alginate matrix, highlighting characteristic HA peaks and alginate's amorphous nature. FTIR analysis validated the composite formation through phosphate-carboxylate interactions. SEM imaging revealed a porous, interconnected structure with embedded HA particles, facilitating cell attachment and proliferation. EDAX confirmed the presence of calcium, phosphorus, and oxygen as primary constituents. In vitro degradation studies showed controlled degradation, with 80 % mass loss by day 3, indicating the composite's suitability for gradual tissue replacement. Hemocompatibility tests revealed minimal hemolysis (<2 %), confirming the composite's excellent blood compatibility. Conclusion: The findings emphasize the potential of Alg-HA scaffolds for dentin regeneration. Their porous architecture, combined with embedded HA, enhances mechanical stability while providing essential biochemical cues for cell proliferation and mineralization. The demonstrated hemocompatibility ensures safe application in direct blood contact, reducing immune responses and promoting tissue integration. Compared to previous studies, this research offers a more in-depth understanding of the relationship between porosity, mineralization, and cellular behavior. Alginate-hydroxyapatite scaffolds exhibit excellent structural, chemical, and biological properties, making them promising candidates for regenerative dentistry. With excellent degradation, hemocompatibility, and ability to support cellular functions, these scaffolds hold significant potential for clinical applications, with further optimization paving the way for broader medical adoption.